2022
DOI: 10.1021/acs.jpclett.2c03422
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Structure and Optoelectronic Properties During Halide Perovskite Vapor Deposition

Abstract: The efficiency of perovskite-based solar cells has increased dramatically over the past decade to as high as 25%, making them very attractive for commercial use. Vapor deposition is a promising technique that potentially enables fabrication of perovskite solar cells on large areas. However, to implement a large-scale deposition method, understanding and controlling the specific growth mechanisms are essential for the reproducible fabrication of high-quality layers. Here, we study the structural and optoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Furthermore, intensity tests of the X-ray beam and laser excitation were made to exclude any detrimental influence (observer effect) on the in situ monitoring. The X-ray fluence was 10 8 photons/cm 2 /s, two orders of magnitude below 10 10 suggested by Held et al [19] to prevent degradation and well below the 10 16 decomposition threshold reported by Svanström et al [22] We did not observe a degradation by illumination either, by comparing the evolution under continuous and discontinuous (30s off, 5s on) light illumination, Figure S12 (Supporting Information). Note, the in situ experiments were conducted with a temperature setpoint at 170°C, enabling a slightly decelerated reaction, allowing for more precise tracking and a faster heating to setpoint, despite the smaller heater.…”
Section: In Situ Study Of Thin Film Growthmentioning
confidence: 54%
See 3 more Smart Citations
“…Furthermore, intensity tests of the X-ray beam and laser excitation were made to exclude any detrimental influence (observer effect) on the in situ monitoring. The X-ray fluence was 10 8 photons/cm 2 /s, two orders of magnitude below 10 10 suggested by Held et al [19] to prevent degradation and well below the 10 16 decomposition threshold reported by Svanström et al [22] We did not observe a degradation by illumination either, by comparing the evolution under continuous and discontinuous (30s off, 5s on) light illumination, Figure S12 (Supporting Information). Note, the in situ experiments were conducted with a temperature setpoint at 170°C, enabling a slightly decelerated reaction, allowing for more precise tracking and a faster heating to setpoint, despite the smaller heater.…”
Section: In Situ Study Of Thin Film Growthmentioning
confidence: 54%
“…are reflected in differences in the crystallographic and optoelectronic properties. We sought to follow the evolution from template to perovskite by making use of the in situ capabilities of GIWAXS, [18] and combining it with optoelectronic insights from photoluminescence monitoring, as proposed by Mrkyvkova and Held et al [19][20][21] The reaction chamber for the in situ setup is designed to mimic the reference chamber closely, yet one notable difference between the setups is the temperature profile. To exclude artefacts introduced hereby, we compared films reacted with different temperature profiles, either with a progressive heating profile or the reference flat temperature profile in Figure S11 (Supporting Information) after the same reaction times.…”
Section: In Situ Study Of Thin Film Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ GIWAXS allows tracking of the formation, fluctuation, and disappearance of the different crystalline phases during evaporation, as well as their orientation with respect to the substrate for the thin films once deposited. Readers interested in this technique are referred to the work of Held et al or the review of Qin et al Energy-dispersive X-ray spectroscopy (EDX) complements this structural information with chemical insights. The resulting metal halide templates are then converted into perovskite thin films and implemented in photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%